Retrospective Analysis of Acute Abdomen Surgeries in Adult Patients Due to Acute Appendicitis and Constricted Hernia During Covid-19 Lockdown in Comparison with the Pre Lockdown Period in A Tertiary Hospital in Western Greece - Dedopoulou, Vivian; Chardalia, Maria; Zacharis, Nada; Potsios, Charalampos; Xaplanteri, Panagiota; Zacharis, Georgios (Archives of Clinical and Medical Case Reports, 2020)
The COVID-19 pandemic led to the imposition of restrictive measures from March 23 to May 4, 2020 in Greece (Lockdown). The Lockdown combined with the fear of the new disease led to the working hypothesis that the attendance of patients with urgent surgical problems may have been affected. The purpose of this study was the retrospective analysis and comparison of emergency surgical cases due to acute appendicitis and constricted hernia admitted to the Department of Surgery of a tertiary hospital in Western Greece. The study period was March-April 2020 in comparison with January-February 2020. January-February 2020: 18 patients met the criteria of the study. None of the patients with acute appendicitis suffered from peritonitis or other complications. None of the patients with constricted hernia required enterectomy. March-April 2020: 17 patients with acute appendicitis and constricted hernia were admitted. Of the patients with acute appendicitis, 20% suffered from peritonitis at the time of diagnosis. Of the patients with tight hernia, 14% required enterectomy. The total number of surgeries did not change significantly pre Lockdown and during the Lockdown period. An increase in the number of complications has been observed during the Lockdown period, possibly due to the delayed quest of medical attention. <gdiv></gdiv>